HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS MENGGAMAT KECAMATAN KLUET TENGAH KABUPATEN ACEH SELATAN TAHUN 2022 - Santika, Deva; Aramico, Basri; Fahdhienie, Farrah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
Diarrhea is an endemic disease in Indonesia and is also a disease that is often accompanied by death and is caused by various factors, one of which is poor environmental sanitation. This study aims to determine the relationship between environmental sanitation and the incidence of diarrhea in children under five in the Menggamat Health Center Work Area, South Aceh Regency in 2022. This research is descriptive analytic with a cross sectional research design. Data were collected using a questionnaire. The population in this study were all mothers of children under five, totaling 227 people. Samples were taken as many as 70 people. Data were analyzed using Chi-Square statistical test. The results showed that the proportion of diarrhea was 58.6%, clean water supply was 61.4%, good feces disposal was 52.9%, infectious diseases were absent 87.1%, preparation and provision of good food was 57.1%. It can be concluded that there is a relationship between the provision of clean water (p value 0.002), feces disposal (p value 0.019), infectious diseases (p value 0.028) and food preparation and provision (p value 0.013) with the incidence of diarrhea in children under five.Keywords: environmental sanitation, diarrhea, toddler